Assistance in Making Organic Fertilizer Made from Organic Waste in Farmer Groups - Reski Praja Putra; Indrayani Indrayani; Lahming Lahming; Amiruddin Hambali; Jusran Jusran (PT. Global Research Collaboration, 2024)
Banggae is a sub-district located in the city of Majene, West Sulawesi. Generally, the livelihoods of the people in this area are farmers and livestock breeders. One of the representatives of the farmer group in the city of Majene expressed their desire to be assisted and trained in making organic fertilizer. This is based on the large amount of agricultural waste that has not been utilized properly, so organic waste has no economic value. Based on the results of the discussion, one of the solutions offered by the community service team as a form of implementing the tri dharma of higher education to overcome partner problems is to provide training and assistance through optimizing the use of local agricultural waste and household organic waste in producing organic fertilizer. Implementation is carried out through counseling, providing materials, and demonstrations. The process of making organic fertilizer in this activity uses materials that are easily obtained in Banggae District, including banana stems, fruit and vegetable waste, leaves, cow dung, goat dung, and rice washing water. The carbon source is a brown sugar solution mixed with effective microorganism 4 (EM4) as a biocultivator. The method applied is anaerobic microaerophilically using tarpaulin as a fermentation place. The fermentation process lasts for 2 weeks. The results of the mentoring show that the Banggae District farmer group can practice making organic fertilizer from household and agricultural waste independently using EM4 as a biocultivator.